5th European Conference on Speech Communication and Technology (Eurospeech 1997) 1997
DOI: 10.21437/eurospeech.1997-527
|View full text |Cite
|
Sign up to set email alerts
|

Using story topics for language model adaptation

Abstract: The subject matter of any conversation or document can typically be described as some combination of elemental topics. We have developed a language model adaptation scheme that takes a piece of text, chooses the most similar topic clusters from a set of over 5000 elemental topics, and uses topic specific language models built from the topic clusters to rescore N-best lists. We are able to achieve a 15% reduction in perplexity and a small improvement in WER by using this adaptation. We also investigate the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…[3][4][12] also reported that using clustering technique either deteriorates or slightly improves the recognition performance. [12] suggested that better smoothing method (e.g. Kneser-Ney smoothing) need to be applied to cluster language models in order to get good performance.…”
Section: ≥ Nmentioning
confidence: 99%
“…[3][4][12] also reported that using clustering technique either deteriorates or slightly improves the recognition performance. [12] suggested that better smoothing method (e.g. Kneser-Ney smoothing) need to be applied to cluster language models in order to get good performance.…”
Section: ≥ Nmentioning
confidence: 99%
“…Previous work in topic adaptation [1,3,4,5,7,10,11] has mainly focused on identifying topic-specific subsets of the training text and building language models from them. The topic language models are linearly interpolated with a general language model built from all of the training text.…”
Section: Introductionmentioning
confidence: 99%
“…In these approaches, new sources of information are used to generate a context-dependent LM which is then merged with a static LM. These new sources of information may come, for instance, from text categorization systems as in [Seymore and Rosenfeld, 1997], from speaker identification systems [Nanjo and Kawahara, 2003], from linguistic analysis systems [Liu and Liu, 2008] or from the application context itself .…”
Section: Motivation For Language Model Adaptationmentioning
confidence: 99%
“…In this regard, there are different ways in which the interpolation weight can be selected: it can be set empirically by minimizing the perplexity in a development stage with data not seen during training [Clarkson, 1999, Tur and; it can also be estimated under some optimization algorithm, such as Expectation Maximization [Daumé et al, 2010] or Maximum A Posteriori (MAP) adaptation [Wang and Stolcke, 2007]; or it can be set dynamically depending on the current situation of the interaction (the topic of the speech, a specific speaker, etc.) [Haidar andO'Shaughnessy, 2012, Seymore andRosenfeld, 1997].…”
Section: Mixture-based Modelsmentioning
confidence: 99%
See 1 more Smart Citation